Samsung / Farah Najihah Mohamad Kamal - Mohamad Kamal, Farah Najihah (2022)
This assignment is about identifying the problem with the product. The company that I have chosen is Samsung Company. From their variety of products, I have chosen Samsung TV to do my analysis. In this case study, I have done the SWOT analysis to identify the strength, weaknesses, opportunities, and threats of the TV. The main problem I identified on this product is the Customer Dissatisfaction on the quality complained by the users. From the problem, I can come up with the best solution which Samsung electronics should concentrate on producing products at high quality because most of the users came to know about the Samsung brand.